Sliding mode observer-based MRAS for direct torque control of induction motor - Alamri, Y. A. (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper proposes a sensorless sliding mode observer based model reference adaptive system applied to a direct torque control of the induction motor drive. The reference model is a sensorless sliding mode observer and the adaptive model is a typical current model. The proposed scheme provides speed and rotor flux estimations with the derivative of rotor flux set as the state of the adaptive mechanism. The simulation results show the effectiveness of the proposed observer compared with the conventional model reference adaptive system.